CONSTRUCTIONS OF GREATNESS IN FOREIGN POLICY: NEO-OTTOMANISM IN TÜRKİYE AND EURASIANISM IN RUSSIA - Jordan, Jonathan; Azzahra, Salwa (UI Scholars Hub, 2023)
Geopolitical changes in the second decade of the 21st century have shifted the centre of international political power. Non-Western political power centres emerged and increased influence as the unipolar world transformed into a multipolar one. In contrast to the Cold War era, where ideology was the main instrument in dealing with Western influence, some contemporary geopolitical power centres carry the perception of historical glory as an important factor in their foreign policy, as demonstrated by Turkey under the leadership of Recep Tayyip Erdoğan with its neo-Ottomanism and Russia under Vladimir Putin with Eurasianism. By using discourse analysis methods on data collected through a literature review, this research finds that the perception of the historical glory of neo-Ottomanism and Eurasianism is important as a political bargaining instrument and shows opposition to Western unipolarity, even though there are differences in the level of coerciveness in the practices implemented by the two countries.